Financial Ratio Analysis Of Tax Management In Manufacturing Companies On The Idx - kadek apriada; I Made Sudiartana (Hikamatzu | Journal of Multidisciplinary, 2025)
Tax management refers to actions taken to legally minimize tax obligations. Legal tax savings can be achieved through appropriate tax management strategies, although the legality depends on the instruments and methods employed. The effectiveness of tax management is reflected in the actual tax paid by a company as reported in its profit and loss statement. Proper execution of tax management is essential to avoid violations of tax regulations and norms. This study aims to examine the influence of profitability, leverage, liquidity, fixed asset intensity, and inventory intensity on tax management in manufacturing companies listed on the Indonesia Stock Exchange during the period 2020–2022. The research population consists of all manufacturing companies listed on the exchange during that period. The sampling method used is purposive sampling, resulting in 85 companies as the research sample. The analytical method applied is multiple linear regression analysis. The results indicate that profitability has a negative effect on tax management, while fixed asset intensity has a positive effect. Meanwhile, leverage, liquidity, and inventory intensity do not have a significant influence on tax management among manufacturing companies listed on the Indonesia Stock Exchange for the years 2020–2022.